Microwave-dried α-Fe2O3 as a highly efficient catalyst for ortho-methylation of phenol with methanol. (15th October 2016) - Huang, Hua; Liu, Junyi; Liu, Xianxiang; Xiao, Jiafu; Zhong, Sheng; She, Xichun; Fu, Zaihui; Yin, Dulin
Graphical abstract: Highlights: A novel α-Fe2 O3 catalyst was prepared by microwave-drying used for methylation of phenol with methanol, demonstrated larger specific surface area, bigger pore volume. Microwave dried α-Fe2 O3 catalyst showed more acidity than air dried α-Fe2 O3, and can be synthesized with good repeatability, stability and conveniently reactivated. Microwave dried α-Fe2 O3 showed good performance of the methylation of phenol with methanol than air dried α-Fe2 O3, and remained high catalytic activity and ortho-selectivity after continuous 2000 h operation at the temperature from 623 K to 653 K. Abstract: A novel α-Fe2 O3 catalyst for the ortho-methylation of phenol with methanol was synthesized by a combination of co-precipitation and microwave drying technologies. The resultant catalyst was characterized by XRD, BET surface area, XPS, TEM, TG-DTG, and NH3 -TPD. As compared with air oven dried α-Fe2 O3 catalyst, the microwave dried one demonstrated larger specific surface area, bigger pore volume, as well as more acidity, and hence exhibited superior catalytic property for the ortho-methylation of phenol with methanol. Under the reaction conditions of 623 K, WHSV 0.8 h −1, and n(phenol):n(methanol):n(water) = 1:2:0.5, the conversion of phenol on microwave dried α-Fe2 O3 was 67.0%, 21 percentage points higher than that of oven dried catalyst, the selectivity of o -cresol was 88.5%, and total ortho-selectivity of o -cresol and 2, 6-xylenol was nearly constant as 99.7%, that is, almost all methyl group in methanol was guided to ortho-C site of OH group in phenol. The microwave dried α-Fe2 O3 catalyst could be synthesized with good repeatability, and conveniently reactivated. The catalyst still remained high catalytic activity after continuous 2000 h operation at the temperature from 623 K to 653 K.